2017
DOI: 10.7754/clin.lab.2016.161003
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphism of MTHFR C677T Influences Susceptibility to HBV-Related Hepatocellular Carcinoma in a Chinese Population: a Case-Control Study

Abstract: MTHFR C677T polymorphism with TT genotype could be a factor that increases the risk of HBVrelated HCC in a Chinese population, especially those with HBV infection duration of more than 20 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Abnormal MTHFR function is related to an imbalance of DNA synthesis, methylation, and cellular replication as well as low folate status in the plasma/red blood cells, resulting in the accumulation of plasma homocysteine, further increasing oxidative stress (P53 oxidative lesions)/endothelial dysfunction. Reduced MTHFR activity is associated with a high-risk for the development of HCC and is correlated with a lower risk of late-stage HCC and favorable survival outcomes in patients with HCC [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal MTHFR function is related to an imbalance of DNA synthesis, methylation, and cellular replication as well as low folate status in the plasma/red blood cells, resulting in the accumulation of plasma homocysteine, further increasing oxidative stress (P53 oxidative lesions)/endothelial dysfunction. Reduced MTHFR activity is associated with a high-risk for the development of HCC and is correlated with a lower risk of late-stage HCC and favorable survival outcomes in patients with HCC [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…MTHFR C677T mutations are associated with reduced enzyme activity. The MTHFR C677T polymorphism with TT genotype may be a factor in the increased risk of HBV-associated HCC in the Chinese population, especially in individuals whose HBV infection has persisted for more than 20 years [ 48 ]. The folate level is mainly affected by the MTHFR C677T polymorphism.…”
Section: Folate and Liver Diseasesmentioning
confidence: 99%
“…A total of nineteen articles were included and 6941 hepatocellular carcinoma patients and 9436 healthy controls were enrolled [13,29,[32][33][34][43][44][45][46][47][48][49][50][51][52][53][54][55][56] (The flow chat of literature selection was showed in Figure 1 and Table S1 (see Table S1, Supplemental Digital Content, which showed the flow chat of literature selection, http://links.lww.com/MD/G441). The characteristics of the included studies were showed in Table 1.…”
Section: The Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Former meta-analyzes in 2014 and 2015 reported the MTHFR rs1801133 polymorphism was associated with an increased risk of HCC, but for the MTHFR rs1801131 polymorphism, no association was observed [30,31] . Since then, controversial results emerged in different regions and ethnicities [13,29,32–34] . In order to reach a more accurate evaluation of these 2 polymorphisms and HCC risk, we performed an update meta-analysis with trial sequential analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation